2011
DOI: 10.1259/bjr/28699097
|View full text |Cite
|
Sign up to set email alerts
|

Primary mucosa-associated lymphoid tissue lymphoma as a pleural mass

Abstract: ABSTRACT. Primary pleural lymphoma is a rare entity that has been described in association with human immunodeficiency virus (HIV) infection or pyothorax. It occurs in only 7% of primary lymphoma cases. We report the case of a 52-year-old male with no history of HIV infection or pyothorax who was diagnosed of obstructive sleep apnoea syndrome (OSAS) and underwent a routine chest X-ray to screen for any organic cause of the symptoms. The radiograph revealed two voluminous masses with extraparenchymatous feature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…CT findings in pleural NHL are similar to those in pleural metastasis or malignant mesothelioma (23)(24)(25). The present study revealed that, in addition to pleural effusion, NHL mainly appears as diffuse pleural thickening and localized nodules or masses on CT scans.…”
Section: Discussionsupporting
confidence: 78%
“…CT findings in pleural NHL are similar to those in pleural metastasis or malignant mesothelioma (23)(24)(25). The present study revealed that, in addition to pleural effusion, NHL mainly appears as diffuse pleural thickening and localized nodules or masses on CT scans.…”
Section: Discussionsupporting
confidence: 78%
“…Occasionally it appears as isolated pleural effusion prior to the development of a demonstrable mass. CT findings of primary pleural lymphoma are similar to those of pleural metastasis or malignant mesothelioma ( 6 , 7 ). For lymphoma occurring in the thorax, Kunimasa et al ( 8 ) described the "thoracic sandwich sign" as an anterior mediastinal mass encasing the superior vena cava and brachiocephalic vein that is unlikely to be caused by other mediastinal malignancies (such as lung cancer, metastatic cancer, germ-cell cancer, and thymoma) because they often quickly invade large mediastinal vessels.…”
Section: Discussionmentioning
confidence: 52%
“…Primary pleural lymphoma, accounting for only 7% of primary lymphoma cases ( 3 ), usually affects patients with HIV infection or chronic pyothorax ( 4 ). Primary pleural lymphoma occurring in immunocompetent patients without history of chronic tuberculous empyema is extremely rare ( 5 , 6 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary pleural lymphoma occurring in immunocompetent patients without history of chronic tuberculosis, empyema or HIV infection is extremely rare [[2], [3], [4]]. It accounts for about 0.3–1% of extranodal lymphoma [1].…”
Section: Discussionmentioning
confidence: 99%